Message - Al-Shamahy, Prof. Hassan Abdulwahab (Universal Journal of Pharmaceutical Research, 2023)
CONSTRUCTIVE CRITICISM Criticism is constructing a judgment on the negative or positive qualities of someone or something. Criticism can range from offhand comments to a detailed written response. Criticism falls into several overlapping types including "theoretical, practical, impressionistic, affective, didactic, or descriptive". Criticism may also refer to expressing disapproval of someone or something. When criticism of this kind is constructive it can make an individual aware of gaps in their own understanding and can provide distinct avenues for improvement. Research supports the idea that the use of feedback and constructive criticism in the learning process has a significant impact. When I receive reviewers' comments on my articles that have been submitted to the journal for publication as they said in good rated journals, I always feel afraid to read their comments because their comments are just excuses for rejecting your research article most of the time or some kind of humiliation. Where I receive the following sentences: After a full investigation of the issue at hand, the Office of Scientific Publications agreed that the article could not be published in our journal. Total 50% of your submitted article has been copied and pasted from various sources which is why I have withdrawn it. Only 2% of articles received in the journal are accepted for further processing. If your research is supported by the NHS: We can consent to further processing. Send it to other journals. Submit it to a local journal etc. All these sentences are reflected in my mind as follows: You are a thief because 50% is copied. There is no support for your search so you should be penalized more. You are one of the 98% of stupid researchers or 98% of researchers are stupid and you are one of them. This is called critique, but it is little more than an offshoot of sermons. They judge a work of art, not by its clarity and truth, not by the force and charm of its ideas, not by the artist's technical virtuosity, not by its originality and artistic courage, but simply and only by its orthodoxy (the word orthodoxy comes from the Greek root words orthos, which means right, true or straight, and doxa, opinion). In our beloved journal (UJPR), criticism builds a judgment on the negative or positive qualities of articles and studies received by the journal, with encouragements responses for researchers such as: there is similarity, please rephrase the sentences - please add this and this, clear sentence please, is this sentence better? etc., so we must continue to encourage researchers everywhere to publish their research as human issues.